Synthesis of spiroannulated dihydroisobenzofuranylated monosaccharides - Maurya, S. K.; Hotha, Srinivas (Tetrahedron Letters, 2006)
An efficient synthesis of spiroannulated dihydroisobenzofurans is achieved using easily accessible carbohydrate-derived furanyl propargyl ethers via an AuCl3 promoted intramolecular Diels-Alder (IMDA) reaction. The scope of the spiroannulation protocol was demonstrated using a diverse range of pentofuranosyl, hexofuransoyl and hexopyranosyl derived substrates in order to synthesize spiroannulated dihydroisobenzofurans. The reaction is high yielding, moisture tolerant, fast and uses only a catalytic amount of AuCl3. (c) 2006 Elsevier Ltd. All rights reserved.